Contrasting Associations Between Heart Rate Variability and Brainstem-Limbic Connectivity in Posttraumatic Stress Disorder and Its Dissociative Subtype: A Pilot Study - Thome, Janine; Densmore, Maria; Terpou, Braeden A.; Théberge, Jean; McKinnon, Margaret C.; Lanius, Ruth A. (Frontiers in Behavioral Neuroscience, 2022)
Background: Increasing evidence points towards the need to extend the neurobiological conceptualization of posttraumatic stress disorder (PTSD) to include evolutionarily conserved neurocircuitries centered on the brainstem and the midbrain. The reticular activating system (RAS) helps to shape the arousal state of the brain, acting as a bridge between brain and body. To modulate arousal, the RAS is closely tied to the autonomic nervous system (ANS). Individuals with PTSD often reveal altered arousal patterns, ranging from hyper- to blunted arousal states, as well as altered connectivity profiles of key arousal-related structures that receive direct projections from the RAS. Accordingly, the present study aims to explore resting state functional connectivity of the RAS and its interaction with the ANS in participants with PTSD and its dissociative subtype. Methods: Individuals with PTSD (n=57), its dissociative subtype (PTSD+DS, n=32) and healthy controls (n=40) underwent a six-minute resting functional magnetic resonance imaging and pulse data recording. Resting state functional connectivity (rsFC) of a central node of the RAS – the pedunculopontine nuclei (PPN) – was investigated along with its relation to ANS functioning as indexed by heart rate variability (HRV). HRV is a prominent marker indexing the flexibility of an organism to react adaptively to environmental needs, with higher HRV representing greater effective adaption. Results: Both PTSD and PTSD+DS demonstrated reduced HRV as compared to controls. HRV measures were then correlated with rsFC of the PPN. Critically, participants with PTSD and participants with PTSD+DS displayed inverse correlations between HRV and rsFC between the PPN and key limbic structures, including the amygdala. Whereas participants with PTSD displayed a positive relationship between HRV and PPN rsFC with the amygdala, participants with PTSD+DS demonstrated a negative relationship between HRV and PPN rsFC with the amygdala. Conclusions: The present exploratory investigation reveals contrasting patterns of arousal-related circuitry among participants with PTSD and PTSD+DS, providing a neurobiological lens to interpret hyper- and more blunted arousal states in PTSD and PTSD+DS, respectively.